Tailoring Vanadium Dioxide Film Orientation Using Nanosheets: a Combined Microscopy, Diffraction, Transport, and Soft X-Ray in Transmission Study - Le P.T.P.; Hofhuis K.; Rana A.; Huijben M.; Hilgenkamp H.; Rijnders G.A.J.H.M.; ten Elshof J.E.; Koster G.; Gauquelin N.; Lumbeeck G.; Schüßler-Langeheine C.; Popescu H.; Fortuna F.; Smit S.; Verbeek X.H.; Araizi-Kanoutas G.; Mishra S.; Vaskivskyi I.; Dürr H.A.; Golden M.S. (My University, 2025)
Vanadium dioxide (VO2) is a much-discussed material for oxide electronics and neuromorphic computing applications. Here, heteroepitaxy of VO2 is realized on top of oxide nanosheets that cover either the amorphous silicon dioxide surfaces of Si substrates or X-ray transparent silicon nitride membranes. The out-of-plane orientation of the VO2 thin films is controlled at will between (011)M1/(110)R and (−402)M1/(002)R by coating the bulk substrates with Ti0.87O2 and NbWO6 nanosheets, respectively, prior to VO2 growth. Temperature-dependent X-ray diffraction and automated crystal orientation mapping in microprobe transmission electron microscope mode (ACOM-TEM) characterize the high phase purity, the crystallographic and orientational properties of the VO2 films. Transport measurements and soft X-ray absorption in transmission are used to probe the VO2 metal–insulator transition, showing results of a quality equal to those from epitaxial films on bulk single-crystal substrates. Successful local manipulation of two different VO2 orientations on a single substrate is demonstrated using VO2 grown on lithographically patterned lines of Ti0.87O2 and NbWO6 nanosheets investigated by electron backscatter diffraction. Finally, the excellent suitability of these nanosheet-templated VO2 films for advanced lensless imaging of the metal–insulator transition using coherent soft X-rays is discussed. © 2019 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim